Expansion of the Hox gene family and the evolution of chordates. - Pendleton, J W (1993)
Homeobox genes encode DNA-binding transcription regulators that participate in the formation of embryonic pattern or contribute to cell-type specificity during metazoan development. Homeobox genes that regulate axial patterning and segmental identity (Hox/HOM genes) share a conserved clustered genomic organization. Mammals have four clusters that have likely arisen from the duplication of a single ancestral cluster. The number of Hox-type genes in other deuterostomes was estimated by using a polymerase chain reaction sampling method. Increased Hox gene complements are associated with the appearance of chordate and vertebrate characters. Our data suggest the presence of one Hox cluster in the acorn worm, a hemichordate; two Hox clusters in amphioxus, a cephalochordate; and three in the lamprey, a primitive vertebrate.